Strategi Positioning “Gemoy” Prabowo Subianto melalui Media Digital - Sihabudin, M. Maulana Rizik; Helwa Nur Alfa Laila; Kharisma Kharis; Rismayanti; Riska Siti Fatimah (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2023)
This research aims to analyze the transformation of Prabowo Subianto's image from a stern and authoritative figure to a more relaxed and attractive one, focusing on the development of a "gemoy" image ahead of the 2024 Indonesian presidential general election.  Using a qualitative methodology and case study approach, the research collected data through documentation, observation, as well as content and discourse analysis from print, electronic, and online media. The study shows that Prabowo's image change is influenced by the current political dynamics, the evolution of information technology, and the changing preferences of voters, especially the younger generation. The main findings show that Prabowo's positioning strategy through digital media, especially on social media platforms such as Twitter, Instagram, and TikTok, plays a crucial role in shaping a new image that is more relaxed and fun. This research provides insights into how politicians can adapt their image to attract voters, especially from the younger generation, in the digital era. The findings also highlight the importance of digital media in contemporary political campaigns, where it is not only a communication tool but also a strategic instrument in political image formation and management. This research contributes to the understanding of the dynamics of political image formation in Indonesia, providing evidence of how images can be strategically altered to achieve greater resonance with voters in a changing political context.